The Influence of Hotel Tax and Restaurant Tax on the Original Regional Income of Garut Regency - Farida, Dida; Hamdah, Latipatul; Wahyuni, Resa Sri (Fakultas Ekonomi Universitas Garut, 2025)
This review is intended to research the reaction of lodging rates and dining rates to local revenue in Garut Regency throughout 2015-2022. The information in this research was obtained from the Garut Regency Regional Revenue Service regarding records of the application of lodging rates and dining rates. The system used in this study is the quantitative one. An interrogation and document verification system was put in place to gather data for this study. Additionally, R-Squared, multiple linear regression analysis, and hypothesis testing with the use of the F and t tests are the procedures utilized in this study. Data computations in this study were performed using the SPSS version 26 for Windows application. The results of this study show that the combined effect of restaurant and hotel taxes on local income is substantial. But upon closer inspection, it turns out that restaurant taxes significantly affect local revenue whereas hotel taxes do not.